Factors influencing adherence to antiretroviral therapy among young adults at clinics around Mankweng Hospital, Limpopo Province, South Africa - Mashele, Victoria (My University, 2024)
Background: The study sought to understand factors influencing adherence to antiretroviral therapy (ART) among young adults accessing HIV care at clinics around Mankweng Hospital located at Capricorn district in Limpopo Province, South Africa. Methods: A descriptive qualitative study design was conducted using individual unstructured interviews to understand factors influencing adherence to antiretroviral therapy among young adults. The study was conducted at three primary care clinics around Mankweng Hospital namely Evelyn Lekganyane, Mankweng gateway and Nobody clinic. Purposive sampling method was used to select participants aged 18 to 35 years, who had been on antiretroviral therapy for more than a year. Data was collected using individual unstructured interviews with an interview guide that included characteristic description of the participants. Open-ended questions were used to explore factors that influence antiretroviral therapy among young adults. Recorded interviews were transcribed verbatim and translated. The coded transcripts were thematically analyzed. Results: Eights major themes were identified, namely (I) medication related factors; (ii) family support; (iii) disclosure; (iv) acceptance of HIV status; (v) economic factors; (vi) reminders; (vii) healthcare worker attitudes and (viii) health system factors were identified as the factors that influence ART adherence among young adults. Conclusion: Adherence to antiretroviral therapy is still a major problem in our communities, and people living with HIV are still finding it challenging to optimally adhere to their ART medication due to the identified factors that influence ART adherence. Family support was one of the significant factors that was identified to positively influence ART as it leads to disclosure and acceptance of HIV positive status, better mental state, and subsequently improved ART adherence. Patients are aware and have recognized the benefits of ART, which motivates them to adhere to treatment despite ART medication related challenges. This study underscores the importance of patient-centred care and family support in the management of HIV and ART adherence. It is important to encourage disclosure and acceptance of HIV status while conducting ART adherence counselling to promote ART adherence.
Thesis (M. Med. (Family Medicine)) -- University of Limpopo, 2024
Keywords: Antiretroviral therapy; Adherence; Factors influencing; Challenges to antiretroviral therapy; Highly active antiretroviral therapy; Antiretroviral agents -- South Africa -- Limpopo; Patient compliance